Customer Perceived Value (Cpv) From The MPI Perspective: Integration Of Academic Service Quality And Blessing Orientation - Muthi'a Rahman; Annisa Tri Ananda Dewi; Uryatul Hikmah; Siti Khofsah; Ittaqillah Haitsuma Kunta; Ida Kusumawati; Najiburrohman Najiburrohman (Universitas Nurul Jadid, 2025)
This study aims to analyze Customer Perceived Value (CPV) in Islamic education management by integrating academic service quality with blessing orientation, highlighting both functional and spiritual dimensions of student experience. A qualitative approach with a case study design was employed, with data collected through documentation, observation, and semi-structured interviews. Analysis followed systematic stages of data reduction, data display, and verification, using content analysis, discourse analysis, and interpretive approaches to capture both rational and experiential insights. Findings indicate that academic service quality significantly contributes to student satisfaction and comfort, while blessing orientation encompasses meaning, serenity, and depth of the learning experience. The integration of these dimensions produces a holistic CPV, extending beyond conventional functional aspects to include emotional and spiritual elements. The study underscores the importance for Islamic educational institutions to harmonize service quality with spiritual values to enhance the overall educational experience, providing a foundation for designing policies and strategies that address students’ comprehensive needs, fostering meaningful, contextually relevant, and spiritually enriching learning environments.